A compact substrate integrated waveguide CRLH leaky-wave antenna for S-band applications - Saravani, Sobhan; Chakrabarty, Chandan Kumar; Norashidah, Md Din; Devi, K. K. A. (2015)
A compact beam scanning substrate integrated waveguide (SIW) composite right/left-handed (CRLH) leaky wave antenna (LWA) is presented in this paper. The dispersive behavior of the unit cell is discussed and compared with its equivalent circuit model. A SIW CRLH LWA that composed of 15-unit cells is designed and its transient e-field distribution for the left-handed, right-handed and transition frequencies are demonstrated by performing a full-wave simulation using CST microwave studio. The proposed antenna is designed to operate within the S-band frequency range exhibiting a continuous backfire to endfire beam scanning of 133 degrees from -68 degree at 2.05GHz up to +65 degree at 3.25GHz for the backward and forward wave radiations, respectively. The numerical results show a relatively high gain with a maximum gain of 8.6dBi at 2.55GHz and low cross-polarization for the entire band.